Discovery of the Darwin wasp subfamily Lycorininae Cushman & Rohwer (Hymenoptera: Ichneumonidae) from India with description of a new species from Kashmir - Ranjith, A.p.; Sheikh, Altaf Hussain; Priyadarsanan, Dharma Rajan (Zootaxa, 2022)
The Darwin wasp subfamily Lycorininae is newly reported from India with the description of a new species, Lycorina sehgali. A taxonomic key to the identification of Indomalayan and Palaearctic species is given along with the illustration of L. ruficornis, L. spilonotae and L. triangulifera.